Water-based inorganic coating composition

By adding tetra-needle zinc oxide whiskers and protective colloid powder to water-based inorganic coatings, the problems of unstable color and insufficient adhesion of colored water-based inorganic coatings are solved, thereby improving the stability, uniformity and breathability of the coating.

CN119331443APending Publication Date: 2025-01-21SICHUAN SANKESHU PAINT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411429189.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing colored water-based inorganic coatings suffer from problems such as pigment particle aggregation, floating color, blooming, and discoloration due to the high pH value of potassium silicate solution. Furthermore, the inorganic coating has insufficient adhesion to the substrate and poor breathability.

Method used

The main components are tetra-needle zinc oxide whiskers and protective colloid powder. The tetra-needle zinc oxide whiskers improve the adhesion and breathability of the inorganic coating to the substrate, while the protective colloid powder improves the dispersibility and stability of the water-based pigment. Combined with other fillers and thickeners, a stable water-based inorganic coating composition is formed.

Benefits of technology

It improves the color stability and uniformity of inorganic coatings, enhances adhesion to the substrate, improves breathability and impact resistance, and avoids problems such as color change and insufficient adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a water-based inorganic coating composition, and relates to the technical field of water-based coatings. The water-based inorganic coating composition is prepared from the following raw material components in percentage by weight: 15 to 25 percent of potassium silicate solution, 5 to 8 percent of polymer emulsion, 0.3 to 0.7 percent of wetting agent, 0.2 to 1 percent of defoaming agent, 0.3 to 1 percent of dispersing agent, 20 to 50 percent of filler, 0.3 to 1 percent of thickening agent, 0.5 to 5 percent of water-based color paste and the balance of water, the weight ratio of the tetrapod-like zinc oxide whiskers in the filler is not less than 5%; the weight ratio of the protective rubber powder in the thickening agent is not less than 25%. After being cured, the water-based inorganic coating composition disclosed by the invention has relatively good impact strength, water vapor permeability, bonding strength and color paste dispersion uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water-based coatings and relates to a water-based inorganic coating composition. Background Art

[0002] Water-based inorganic coatings with potassium silicate solution as the main film-forming substance have the characteristics of low VOC content, good weather resistance and easy cleaning. However, for colored water-based inorganic coatings, the pH of potassium silicate solution is relatively high (pH is 11-12), which will destroy the wetting and dispersion layer of the water-based color paste, causing the aggregation of pigment particles. The hue index of the water-based coating will slowly change, and problems such as floating color, flowery and discoloration will occur. In addition, the formed inorganic coating also needs to increase the bonding strength with the substrate (such as putty layer, concrete layer, etc.) and have high air permeability.

[0003] Therefore, the existing water-based inorganic coatings need to be further improved. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a water-based inorganic coating composition.

[0005] The technical solution of the present invention is as follows:

[0006] A water-based inorganic coating composition, wherein the raw material components, by weight, include 15-25% potassium silicate solution, 5-8% polymer emulsion, 0.3-0.7% wetting agent, 0.2-1% defoamer, 0.3-1% dispersant, 20-50% filler, 0.3-1% thickener, 0.5-5% water-based color paste, and the balance is water;

[0007] The weight proportion of the tetrapod-shaped zinc oxide whiskers in the filler is not less than 5%;

[0008] The weight proportion of the protective rubber powder in the thickener is not less than 25%.

[0009] Preferably, the weight proportion of the four-needle zinc oxide whiskers in the filler is not higher than 30%.

[0010] Preferably, the filler further comprises one or a combination of two or more of diatomaceous earth, calcined kaolin, barium sulfate and calcium sulfate whiskers.

[0011] More preferably, the weight proportion of the calcium sulfate whiskers in the filler is 1-5%.

[0012] Preferably, the weight proportion of the protective rubber powder in the thickener is no more than 50%.

[0013] Preferably, the protective rubber powder is selected from magnesium aluminum silicate and / or magnesium lithium silicate.

[0014] Preferably, the thickener further comprises cellulose ether and / or associative polyurethane thickener.

[0015] Preferably, the polymer emulsion is selected from one or a combination of two or more of styrene acrylic emulsion, acrylic emulsion, epoxy modified acrylic emulsion and silicone modified acrylic emulsion.

[0016] Preferably, the raw material components further comprise one or a combination of two or more of a preservative, a bactericide, an anti-ultraviolet agent, an anti-yellowing agent and an anti-settling agent.

[0017] The beneficial effects of the present invention are:

[0018] (1) The filler used in the water-based inorganic coating of the present invention contains tetrapod-shaped zinc oxide whiskers, which can improve the adhesion and air permeability of the inorganic coating to the substrate, and can further improve the air permeability of the inorganic coating when combined with calcium sulfate whiskers.

[0019] (2) The thickener used in the water-based inorganic coating of the present invention contains protective rubber powder, which can better improve the dispersibility and stability of the color paste particles in the coating, and is not prone to color problems such as floating color, blooming, and discoloration. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0021] In order to improve the bonding force of the inorganic coating to the substrate and the air permeability of the inorganic coating on the basis of solving the problem of unstable color of the water-based inorganic coating, the present invention provides a water-based inorganic coating composition, wherein the raw material components, by weight, include 15-25% potassium silicate solution, 5-8% polymer emulsion, 0.3-0.7% wetting agent, 0.2-1% defoaming agent, 0.3-1% dispersant, 20-50% filler, 0.3-1% thickener, 0.5-5% water-based color paste, and the balance is water;

[0022] The weight proportion of tetrapod-shaped zinc oxide whiskers in the filler is not less than 5%;

[0023] The weight proportion of protective rubber powder in the thickener is not less than 25%.

[0024] Tetrapod-shaped zinc oxide whiskers have a unique three-dimensional tetrapod-shaped structure, can be easily dispersed in a matrix material, and can isotropically improve the properties of the matrix material. Waterborne inorganic coatings are usually applied to the surface of substrates such as putty layers and concrete layers. In the present invention, adding tetrapod-shaped zinc oxide whiskers to the waterborne inorganic coating has the following effects: (1) It can improve the bonding strength of the inorganic coating to the substrate, making the performance of the inorganic coating more stable and the service life longer. The possible reason is that at the junction of the inorganic coating and the substrate, the ends of each needle of the tetrapod-shaped zinc oxide whisker are like anchor points, which improves the bonding strength of the inorganic coating to the substrate; (2) It can improve the air permeability of the inorganic coating, which helps the water vapor in the substrate to evaporate into the atmosphere faster through the inorganic coating. The low water vapor content of the bottom layer is also conducive to maintaining the high adhesion and long service life of the inorganic coating; (3) The good dispersibility of the tetrapod-shaped zinc oxide whiskers can also improve the uniform dispersion of the waterborne color paste in the waterborne inorganic coating, so that the color of the waterborne inorganic coating is more uniform and the color difference of different parts is very low; (4) The isotropic performance of the tetrapod-shaped zinc oxide whiskers can improve the impact resistance of the inorganic coating.

[0025] Adding protective rubber powder to the thickener can improve the stability of the added water-based color paste in the water-based inorganic coating, and avoid the stability of the water-based color paste being destroyed due to the high alkalinity of potassium silicate. The protective rubber powder combined with the four-needle zinc oxide whisker makes the water-based inorganic coating of the present invention have obvious improvements in color stability, uniformity, etc.

[0026] In a preferred embodiment of the present invention, the weight proportion of the four-needle zinc oxide whisker in the filler is not higher than 30%. If the weight proportion of the four-needle zinc oxide whisker is too low, the action and effect are not obvious. If the weight proportion of the four-needle zinc oxide whisker is too high, it will affect other properties of the inorganic coating, such as mechanical strength. For example, the weight proportion of the four-needle zinc oxide whisker in the filler can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 27%, 30%, etc., or any value in between, without special restrictions. In the present invention, the four-needle zinc oxide whisker can be purchased directly from the market, such as Hangzhou Jikang New Materials Co., Ltd., Wuhu Xinda New Materials Technology Co., Ltd., etc.

[0027] In a preferred embodiment of the present invention, the filler further comprises one or a combination of two or more of diatomaceous earth, calcined kaolin, barium sulfate and calcium sulfate whisker. In addition to the filling function, the filler also has a reinforcing function. Different fillers have different reinforcing functions, and the filler can be selected according to performance requirements.

[0028] In a more preferred embodiment of the present invention, the weight proportion of calcium sulfate whiskers in the filler is 1-5%. Calcium sulfate whiskers combine the advantages of reinforcing fibers and ultrafine inorganic fillers, and can be interlaced with four-needle zinc oxide whiskers when dispersed in water-based inorganic coatings, generating interactions in space, and thus having a synergistic effect, which can further improve the impact resistance and air permeability of the inorganic coating. For example, the weight proportion of calcium sulfate whiskers in the filler can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., or any value in between, without special restrictions. In the present invention, calcium sulfate whiskers can be purchased directly from the market, such as Shanghai Fengzhu Composite New Material Technology Co., Ltd. or Suzhou Hengnaida New Material Co., Ltd.

[0029] In a preferred embodiment of the present invention, the weight proportion of the protective rubber powder in the thickener is not higher than 50%. If the weight proportion of the protective rubber powder in the thickener is insufficient, the effect cannot be manifested or is not obvious. If the weight proportion of the protective rubber powder in the thickener is too high, it is not good for the stability of the water-based color paste. For example, the weight proportion of the protective rubber powder in the thickener can be any value of 25%, 27%, 30%, 33%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, etc. or any value in between, without special restrictions.

[0030] In a preferred embodiment of the present invention, the protective rubber powder is selected from magnesium aluminum silicate and / or magnesium lithium silicate. Magnesium aluminum silicate and magnesium lithium silicate have unique gelling properties, thickening properties, thixotropy, rheology, adsorption properties, stability, and suspension and anti-settling properties, which can effectively improve the stability of the water-based color paste after being added to the water-based inorganic coating, and prevent the dispersed structure of the water-based color paste from being destroyed by the higher alkalinity of potassium silicate.

[0031] In a preferred embodiment of the present invention, the thickener further comprises cellulose ether and / or associative polyurethane thickener. The thickener in the present invention has good thickening, thixotropic and protective effects through the combination of organic thickener and inorganic thickener. Cellulose ether can be directly purchased from the market, for example, HE 3KB Plus 550 thickener from Ashland, USA.

[0032] In a preferred embodiment of the present invention, the polymer emulsion is selected from one or a combination of two or more of styrene-acrylic emulsion, acrylic emulsion, epoxy-modified acrylic emulsion and silicone-modified acrylic emulsion. The polymer emulsion can further be a styrene-acrylic emulsion, which can be directly purchased from the market, such as Rosf ROSF-5588, Baderfu RS-837A, and Baolijia BLJ-WG1809A.

[0033] In a preferred embodiment of the present invention, the raw material components further include one or a combination of two or more of a preservative, a bactericide, an anti-ultraviolet agent, an anti-yellowing agent and an anti-settling agent, which can further improve the comprehensive performance of the inorganic coating.

[0034] The technical solution of the present invention is further described and illustrated according to various embodiments below. Unless otherwise specified, the parts described in the following embodiments are parts by weight.

[0035] Example 1

[0036] A water-based inorganic coating composition, wherein the raw material components are 100% by weight, including: 20% potassium silicate solution (concentration 28wt%), 6% styrene acrylic emulsion, 0.4% wetting agent BYK-345, 0.8% defoamer BYK-021, 0.7% dispersant BYK-2013, 40% filler, 0.5% thickener, 2% water-based blue color paste, and the balance is water;

[0037] The filler consists of tetrapod-shaped zinc oxide whiskers, diatomaceous earth, calcined kaolin and barium sulfate in a weight ratio of 1:1:2:1.

[0038] The thickener is composed of lithium magnesium silicate and cellulose ether HE 3KB Plus 550 in a weight ratio of 1:2.

[0039] Add water, dispersant, wetting agent and defoamer into a disperser, stir and disperse at 800 rpm for 15 minutes, add filler and water-based color paste, stir and disperse at 1500 rpm for 20 minutes, then add potassium silicate solution, styrene acrylic emulsion and other raw material components, stir and disperse at 600 rpm for 15 minutes to obtain.

[0040] Example 2

[0041] The difference between this embodiment and embodiment 1 is that compared with embodiment 1, the weight proportion of tetrapod-shaped zinc oxide whiskers in the filler is adjusted from 20% to 5%, and the weight proportion of calcined kaolin is adjusted from 40% to 55%. The other steps remain unchanged.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that compared with embodiment 1, the weight proportion of tetrapod-shaped zinc oxide whiskers in the filler is adjusted from 20% to 30%, and the weight proportion of calcined kaolin is adjusted from 40% to 30%. The other steps remain unchanged.

[0044] Example 4

[0045] The difference between this embodiment and embodiment 1 is that compared with embodiment 1, calcium sulfate whiskers are added to the filler, the weight proportion of calcium sulfate whiskers in the filler is 5%, and the weight proportion of calcined kaolin is reduced by 5%. The other steps remain unchanged.

[0046] Example 5

[0047] The difference between this embodiment and embodiment 1 is that compared with embodiment 1, calcium sulfate whiskers are added to the filler, the weight proportion of calcium sulfate whiskers in the filler is 1%, and the weight proportion of calcined kaolin is reduced by 1%. The other steps remain unchanged.

[0048] Comparative Example 1

[0049] The difference between this comparative example and Example 1 is that compared with Example 1, tetrapod-shaped zinc oxide whiskers are not added, the weight proportion of calcined kaolin is adjusted from 40% to 50%, and the weight proportion of diatomaceous earth is adjusted from 20% to 30%. The other steps remain unchanged.

[0050] Comparative Example 2

[0051] The difference between this comparative example and Example 1 is that compared with Example 1, the four-needle zinc oxide whiskers are replaced by calcium oxide whiskers with an equal weight ratio. The other steps remain unchanged.

[0052] Comparative Example 3

[0053] The difference between this comparative example and Example 1 is that compared with Example 1, the tetrapod-shaped zinc oxide whiskers are replaced with calcium oxide whiskers with a filler weight ratio of 10%, and the weight ratio of calcined kaolin is adjusted from 40% to 50%. The other steps remain unchanged.

[0054] Example 6

[0055] The difference between this embodiment and embodiment 1 is that compared with embodiment 1, the thickener is adjusted to be composed of lithium magnesium silicate and cellulose ether HE 3KB Plus 550 in a weight ratio of 1:3. The other steps remain unchanged.

[0056] Example 7

[0057] The difference between this embodiment and embodiment 1 is that compared with embodiment 1, the thickener is adjusted to be composed of lithium magnesium silicate and cellulose ether HE 3KB Plus 550 in a weight ratio of 1:1. The other steps remain unchanged.

[0058] Comparative Example 4

[0059] The difference between this comparative example and Example 1 is that compared with Example 1, the thickener is adjusted to consist entirely of cellulose ether HE3KB Plus 550. The other steps remain unchanged.

[0060] Example 8

[0061] A water-based inorganic coating composition, wherein the raw material components are 100% by weight, including: 25% potassium silicate solution (concentration 28wt%), 8% styrene acrylic emulsion, 0.5% wetting agent BYK-345, 0.8% defoamer BYK-021, 0.9% dispersant BYK-2013, 35% filler, 0.6% thickener, 1.5% water-based red color paste, and the balance is water;

[0062] The weight proportion of the tetrapod-shaped zinc oxide whiskers in the filler is 25%, and the rest of the filler is composed of diatomaceous earth, calcined kaolin and barium sulfate in a weight ratio of 1:2:2.

[0063] The thickener is composed of lithium magnesium silicate and cellulose ether HE 3KB Plus 550 in a weight ratio of 1:2.

[0064] Example 9

[0065] The difference between this embodiment and embodiment 8 is that compared with embodiment 8, calcium sulfate whiskers accounting for 3% of the weight of the filler are added to the filler, and the weight ratio of the remaining fillers is reduced accordingly (the weight ratio remains unchanged). The remaining steps remain unchanged.

[0066] Example 10

[0067] The difference between this embodiment and embodiment 9 is that compared with embodiment 9, the weight proportion of the tetrapod-shaped zinc oxide whiskers in the filler is adjusted from 25% to 10%, the weight proportion of the calcium sulfate whiskers is adjusted from 3% to 1%, and the weight proportions of the remaining fillers are adjusted accordingly (the weight ratio remains unchanged). The remaining steps remain unchanged.

[0068] Embodiment 11

[0069] The difference between this embodiment and embodiment 9 is that compared with embodiment 9, the weight proportion of the tetrapod-shaped zinc oxide whiskers in the filler is adjusted from 25% to 30%, the weight proportion of the calcium sulfate whiskers is adjusted from 3% to 5%, and the weight proportions of the other fillers are adjusted accordingly. The other steps remain unchanged.

[0070] Performance Testing

[0071] The water-based inorganic coating to be tested was applied to the concrete surface by roller brush and cured at room temperature for 96 hours, with an average film thickness of 150 μm.

[0072] Impact resistance: Tested according to the method of GB / T22374-2018.6.3.10, the highest impact strength at which the inorganic coating does not produce cracks is tested. The higher the highest impact strength, the stronger the impact resistance.

[0073] Water vapor transmission rate: Tested according to the method of GB / T 15331-2020. The water-based inorganic coating to be tested is applied to the surface of the PET film layer and cured. The thickness of the inorganic coating is 50 μm. The inorganic coating is removed and tested.

[0074] Bond strength: Tested according to the method of GB / T 9779-2015.

[0075] Color paste dispersion uniformity: The water-based inorganic coating to be tested is sprayed onto a 10-square-meter concrete surface and cured at room temperature for 96 hours, with an average film thickness of 300 μm. The concrete surface is divided into four parts, top, bottom, left, and right, and the average color difference of the four corners, the middle, the middle of the upper part, the middle of the lower part, the middle of the left part, and the middle of the right part is tested, with the △E of the middle position as the reference.

[0076] The performance test results are shown in Table 1 below.

[0077] Table 1

[0078]

[0079]

[0080] From the data results in Table 1 above, it can be seen that the water-based inorganic coating of the present invention adds four-needle zinc oxide whiskers, and after film formation, it has good impact strength, water vapor permeability, bonding strength and color paste dispersion uniformity, and after adding calcium sulfate whiskers, the inorganic coating has higher impact strength and air permeability.

[0081] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

Claims

1. A water-based inorganic coating composition, characterized in that: The raw material components are 100% by weight, Including 15-25% potassium silicate solution, 5-8% polymer emulsion, 0.3-0.7% wetting agent, 0.2-1% defoaming agent, 0.3-1% dispersant, 20-50% filler, 0.3-1% thickener, 0.5-5% water-based color paste, and the balance is water; The weight proportion of the tetrapod-shaped zinc oxide whiskers in the filler is not less than 5%; The weight proportion of the protective rubber powder in the thickener is not less than 25%.

2. The aqueous inorganic coating composition according to claim 1, characterized in that The weight proportion of the four-needle zinc oxide whiskers in the filler is no more than 30%.

3. The aqueous inorganic coating composition according to claim 1, characterized in that The filler further comprises one or a combination of two or more of diatomaceous earth, calcined kaolin, barium sulfate and calcium sulfate whisker.

4. The aqueous inorganic coating composition according to claim 3, characterized in that: The weight proportion of the calcium sulfate whiskers in the filler is 1-5%.

5. The aqueous inorganic coating composition according to claim 1, characterized in that: The weight proportion of the protective rubber powder in the thickener is not higher than 50%.

6. The aqueous inorganic coating composition according to claim 1, characterized in that: The protective rubber powder is selected from magnesium aluminum silicate and / or magnesium lithium silicate.

7. The aqueous inorganic coating composition according to claim 1, characterized in that: The thickener further comprises a cellulose ether and / or an associative polyurethane thickener.

8. The aqueous inorganic coating composition according to claim 1, characterized in that: The polymer emulsion is selected from one or a combination of two or more of styrene acrylic emulsion, acrylic emulsion, epoxy modified acrylic emulsion and silicone modified acrylic emulsion.

9. The aqueous inorganic coating composition according to claim 1, characterized in that: The raw material components also include one or a combination of two or more of a preservative, a bactericide, an anti-ultraviolet agent, an anti-yellowing agent and an anti-settling agent.